Phenylpropanoid derivatives from Ficus esquiroliana and their chemotaxonomic significance. (December 2022) - Dai, De-Cai; Xu, Xue-Feng; Yan, Hao; Zhang, Yu
Abstract: The phytochemical investigation of the stems of Ficus esquiroliana Levl. Led to the isolation of a new phenylpropanoid derivative phenyliana (1 ), together with nine known biogenetically related phenylpropanoid derivatives, chlorogenic acid (2 ), decursidate (3 ), p -hydroxyphenethyl trans -ferulate (4 ), p -hydroxyphenethyl- p -coumarate (5 ), trans -ferulic acid (6 ), trans -caffeic acid (7 ), trans -caffeic acid methyl ester (8 ), trans -cinnamic acid (9 ), and ( E )- p -coumaric acid (10 ). Their structures were elucidated using comprehensive spectroscopic methods. All compounds were isolated from the F. esquiroliana for the first time. The chemotaxonomic significance of the isolated compounds was also discussed. Graphical abstract: Image 1 Highlights: 1. A new and nine known phenylpropanoid derivatives were isolated. 2. Compounds 1 –10 were isolated from the F. esquiroliana for the first time. 3. Compounds 1–5 were newly identified in the family Moraceae, which can be considered a characteristic component of F. esquiroliana.